THE CHALLENGE OF COMBATING TAX EVASION AND ITS IMPACT ON REVENUE, CASE OF THE DGI/MANIEMA FROM 2022 TO 2024 - AMISI SAIDI René Ahmed; BAMBALATI SABITI Janvier; et UTSHUDI LOKADI Aimé (IJRDO - Journal of Business Management, 2025)
This thesis focuses on the issue of combating tax fraud and its impact on public revenue, with a case study of the Provincial Tax Directorate (DPI) of Maniema from 2022 to 2024. In a context of weak domestic resource mobilization, tax fraud poses a major obstacle to the province’s economic development. The study analyzes the mechanisms implemented to counter fraud, assesses their effectiveness, and examines their real impact on tax revenues collected. It highlights structural, institutional, and operational limitations that hinder the performance of the provincial tax administration. The aim is to propose strategies to strengthen tax governance for better public resource mobilization in Maniema.